PERSPECTIVES OF DEVELOPMENT OF MAGNETIC CONTROL OF THE LARGE-SIZE CAST IRON CASTINGS STRUCTURE - S. G. Sandomirskij (Литьë и металлургия)
The results of modern investigations and developments by magnetic control of articles structures by means of “point pole” are given.